Information Technology and World Politics - Mazarr, Michael J. author. aut Link
VI, 187 p. 5 illus.
Keywords: This unique collection of essays explores the intricacies of how the Internet has changed the way we currently approach international security, civil society, and economic development. The contributors move past the conventional wisdom, tapping new and original sources to investigate new and unexpected developments. One essay explores how wiring Russia's nuclear scientists into the Internet increases the threat of weapons proliferation. Another looks at Internet-enabled development projects and, despite early success stories in Bangalore, India, explains why they will fail. Together the essays in this collection try to bring a dose of reality to the rose-colored futures many have predicted for world politics in the Information Age.